Effects of silver incorporation on electrical and optical properties of CuAlxOy thin films - Tran Ngoc Lan; Nguyen Tran Thuat; Hoang Ngoc Lam Huong; Nguyen Van Quynh (Journal of Military Science and Technology, 2022)
The transparent conductive property based on Ag-doped delafossite nanomaterials are attractive for optical sensing applications due to their good electrical conductivity, good optical transparent and high temperature coefficient of resistance. Several delafossite nanomaterials and Ag-doped nanomaterials have been reported, however, Ag-doped delafossite nanomaterials have not been explored, especially regarding the electrical property with high temperature coefficient of resistance. In this study, Ag-doped delafossite CuAlxOy thin films were deposited by co-sputtering techniques. The electrical properties were carried out on a 4-point prober. The optical properties were characterized on an UV-VIS spectrometer. The results on CuAlxOy doped Ag thin films showed that CuAlxOy doped Ag can be hardly applied for transparent conductive layers. However, these films exhibited relatively high temperature coefficient of resistance of about 3%/K, thus being suitable for applications in microbolometers.